Implementasi Forward Chaining Pada Sistem Pakar Sebagai Basis Informasi Persebaran Penyakit Padi - Yenni Fatman; Rodianti Rodianti; Isbandi Isbandi; Rahmini Rahmini; Laila Nur (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2021)
Rice (Oriza sativa L) is the staple food crop for most of the population in Indonesia. In rice crops there can be crop failure, one of the causes of crop failure is rice plant disease. Every disease generally has symptoms that point to the disease itself, these symptoms can be recognized by diagnosis. Due to the lack of knowledge of farmers and limited experts in an area to diagnose diseases, an expert system for diagnosing rice plant diseases is here to provide solutions for alternative diagnoses of rice plant diseases. In this case, implementing the forward chaining method in the expert system to get the results of diagnosis of rice diseases besides that this expert system will find out geographical information on the spread of rice plant diseases in real time by taking the user's location in an area. This expert system for diagnosing rice plant diseases is a web-based application that uses the Laravel framework and for data storage using MySQL. In tests that have been carried out by experts, the accuracy value is 100%.